Implementasi Manajemen Pelayanan untuk Meningkatkan Mutu Pendidikan Program Tahfidz Qur’an Pondok Pesantren Ziyadatut Taqwa Asem Manis 1 Larangan Tokol - Ibniyatus Shalihah; Abd. Ghofur (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this study was conducted at the Ziyadatut Taqwa Islamic Boarding School, which is none other than to improve the quality of Quran memorization education at the Ziyadatut Taqwa Girls' Islamic Boarding School, the research used here uses a qualitative descriptive method, through interviews, observations and documentation, the results of this study indicate that a management service at the Ziyadatut Taqwa Islamic Boarding School can provide the necessary infrastructure based on the needs of Quran memorization at the Islamic Boarding School, both in terms of what is needed or not, service management has its own characteristics in accordance with the vision and mission in Quran memorization, although each Islamic boarding school has different goals, the main goal remains focused on how the quality of Quran memorization in the future will increase and more and more students will memorize the Quran.